Region and Networks: multidimensional and multilevel approaches to analyze the health regionalization process in Brazil - Ana Luiza d'Ávila Viana; Aylene Bousquat; Maria Paula Ferreira; Maria Alice Bezerra Cutrim; Liza Yurie Teruya Uchimura; Edgar Rodrigues Fusaro; Miriam Regina de Souza; Paulo Henrique dos Santos Mota; Ana Paula Chancharulo de Morais Pereira; Fabíola Lana Iozzi; Mariana Vercesi de Albuquerque
Abstract Objectives: to present a methodology used by the Policy, Planning and Region Management research and the Health Care Networks in Brazil - the Regions and Networks research. Methods: description of the analytical scheme in the process of choosing health regions and criteria to select cities and health units, instruments for collecting primary and secondary data and the indicators database, besides the regional typology elaborated for data analysis. Results: the analytical scheme is based on the health policy analysis; policy, structure and organization were defined as the macro dimensions. For each one of these, sub-dimensions were defined. The questionnaire was elaborated by variables that were possible to analyze the regionalization process determinants. Five health regions were selected from the previously defined criteria. Conclusions: the method allowed to establish attributes in the regionalization, constructed by specific components - integration, coordination and regulation. The multilevel approach was important because it portrayed different perceptions from the stakeholder managers and providers according to their bonds in the city, regional and state scenarios.